Changes in Art Textiles Exhibited at International and National Exhibitions in the Meiji Era - Nakagawa, Asako (Bulletin of Japanese Society for the Science of Design, 2012)
This paper reports changes in "Art Textiles" exhibited at national industrial exhibitions and international expositions held in the late Meiji era. Because of high evaluation of earlier works exhibited at the Chicago Exposition of 1893, painting.like textiles were exhibited at the fourth national industrial exhibition of 1895, and were greatly praised. "Art Textiles" reached its peak at that time. In this paper, this is called "the eartly period Art Textiles". However, Japanese textiles did not succeed in receiving recognition as "Art" in the Paris Exposition of 1900. "Art Textiles" then became gradually smaller in size and returned to goods for practical use. In this paper, this is called "the later period Art Textiles". As the result of having analyzed the exhibitor, it turned out that most "Art Textiles" of Meiji Era were made by the contractors in Kyoto, and the specific contractors were mainly making them.